COLONIAL CONFLICTS IN AFRICA IN THE ROMANIAN DIPLOMATIC CORRESPONDENCE (1878-1914). GENERAL CONSIDERATIONS / LES CONFLITS COLONIAUX D’AFRIQUE DANS LA CORRESPONDANCE DIPLOMATIQUE ROUMAINE (1878-1914). CONSIDÉRATIONS GÉNÉRALES - LEAHU, Gabriel (Studia Universitatis Babes-Bolyai Studia Europaea, 2015)
This article analyses the African colonial expansion from the late 19th century to the early 20th century as presented in the Romanian diplomatic correspondence. The aim of our initiative is to highlight to what extent and in what perspective, the competition of the Great Powers in Africa had interested Romania, a European state without any involvement or opportunity to work abroad. On another level, we have been able to observe how aspects of world history are presented in the Romanian diplomatic documents archived by the Ministry of Foreign Affairs. At the same time, it is obvious that Romanian diplomatic documents provide the necessary nuances, confirmations and additions to what was known about the foreign collections of documents and archive material used by the works of foreign historians, completing in a positive way the image of the mentioned period.